1975
DOI: 10.1017/s0043174500052899
|View full text |Cite
|
Sign up to set email alerts
|

Response of Yellow Nutsedge and Soybeans to Bentazon, Glyphosate, and Perfluidone

Abstract: Laboratory, greenhouse, and field experiments were conducted in 1972 and 1973 on the efficacy of controlling yellow nutsedge (Cyperus esculentusL.) in soybeans [Glycine max(L.) Merr.] with bentazon [3-isopropyl-1H-2,1,3-benzothiadiazin-(4)3H-one 2,2-dioxide], glyphosate [N-(phosphonomethyl)glycine], and perfluidone [1,1,1-trifluoro-N-[2-methyl-4-(phenylsulfonyl)phenyl] methanesulfonamide]. Young nutsedge plants (four- to six-leaf stage) were more susceptible to foliar sprays of the three herbicides than were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 8 publications
5
45
0
Order By: Relevance
“…Another possible reason could be the biotype of C. esculentus . Phenological and physiological variations among C. esculentus populations or biotypes could result in differences in growth, reproduction and response to herbicide (Stoller et al. , 1975; Costa & Appleby, 1976; Horak et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason could be the biotype of C. esculentus . Phenological and physiological variations among C. esculentus populations or biotypes could result in differences in growth, reproduction and response to herbicide (Stoller et al. , 1975; Costa & Appleby, 1976; Horak et al.…”
Section: Discussionmentioning
confidence: 99%
“…These perennials have a remarkable ability to survive adverse conditions and then grow explosively under favourable conditions (Tumbleson & Kommedahl, 1961). Cyperus impact varies with location, probably due to differences in climate, crop rotation or biotype (Stoller et al. , 1975; Costa & Appleby, 1976; Keeley et al.…”
Section: Introductionmentioning
confidence: 99%
“…Etheridge and Mueller () and Rotteveel and Naber () found that sequential applications of glyphosate and bentazon were required to provide effective C. esculentus control. Good coverage of the foliage by bentazon sprays is essential, because the bentazon frequently kills only the foliage contacted by the spray (Stoller et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Our results are in line with Stoller et al . (), who reported unsatisfactory C. esculentus control in the field with glyphosate rates below 2200 g a.i. ha −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Since sprouting of tubers was not influenced by the experimental crops, the effect of crop choice may be expected to complement the effects of herbicides, applied to control the weed by killing sprouted tubers. In this stage of the life history C. esculentus is most susceptible to chemical control (Stoller, Wax & Matthiesen, 1975;Pereira et al, 1987). Secondly, by pursuing a dense crop cover during a long period of the growing season the decrease in growth and reproduction of the weed will be enhanced.…”
Section: Discussionmentioning
confidence: 99%